The effectiveness of Sufi music for mental health outcomes. A systematic review and meta-analysis of 21 randomised trials - R.N. Gurbuz- Dogan; A. Ali; B. Candy; M. King (Complementary Therapies in Medicine, 2021)
Background: There is some evidence that Sufi music therapy might improve physical and mental well-being; however, no systematic review or meta-analysis has pooled and critiqued the evidence. The aim of this systematic review was to evaluate the effects of Sufi music therapy on mental health outcomes. Methods: We searched Medline, PsycINFO, the Web of Science, Science Direct, PsycARTICLES, Cochrane Library, SCOPUS, CINAHL Plus, AMED, and ULAKBIM databases, and the reference lists of the studies found. Papers published in academic peer-reviewed journals were included, as well as from other sources such as chapters in edited books, the grey literature, or conference presentations. Articles published up to March 2020 in Turkish and English were included. Our primary outcome of interest was anxiety and secondary outcomes of interest were other mental health outcomes such as depression. To assess the methodological quality of the articles, the Cochrane Risk of Bias Tool was used. The quality of evidence was assessed using the GRADEpro GDT system. Results: This search yielded 21 clinical trials that were eligible for inclusion. A meta-analysis, using a random effects model, of 18 randomised controlled trials involving 1454 participants showed that Sufi music therapy with makams, compared with treatment as usual (TAU) or a no-music control group, reduced symptoms of anxiety in the short term in patients undergoing an operation or treatments such as chemotherapy or haemodialysis (standardised mean difference SMD= −1.15, 95 % CI, −1.64 to −0.65; very low-quality evidence). The evidence of Sufi music with makam's effect on anxiety is rated as very low. Qualitative synthesis of secondary outcomes revealed significant effects for depression, positive symptoms in schizophrenia, stress, which however were based on fewer studies. Trials were of moderate methodological quality, and there was significant heterogeneity across the studies. Conclusion: Sufi music may reduce anxiety of patients undergoing medical procedures like haemodialysis, coronary artery surgery, angiography, colonoscopy, bone marrow aspiration and biopsy procedures. Evidence from single studies suggests effects on depression and stress as well. However, due to methodological limitations of the studies, further, higher quality studies are required in other cultures.